Kehendak Buta Perspektif Schopenhauer - I Nyoman Surpa Adisastra; i Putu Sinta Oktaviani; Luh Kartika Dewi (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2021)
, Arthur Schopenhauer was a German philosopher who continued the post-Kant tradition of philosophy. Kant's thoughts emerge in Schopenhauer's view of the world as ideas and wills. Kant stated that human knowledge is limited to the realm of appearances or phenomena, so that things in him (das Ding an sich) can never be known to humans. The thought of the world as I want it to be, life is full of suffering, and it would be so much better if it wasn't born. Some people seem pessimistic, including Arthur Schopenhauer. "The world as a representation" is the construction of our reality in the mind. This is what Kant calls the world of phenomena. Look around you now. Maybe you can see a tree, a person or a car through the window, or a book in front of you; maybe you can hear birds or traffic or noises in other rooms. What you experience through your senses is the world as a representation. The will is evil, according to Schopenhauer. Because the will implies desire, and what is desired is always greater and more than what is obtained. Desire is always unlimited, while its fulfillment is always limited. Life is evil because once desire and suffering disappear from man, boredom replaces desire and suffering. Increased knowledge does not mean freedom from suffering, but increasing suffering. Talented humans are the ones who suffer the most. Keyword: will as a crime, desire full of suffering.